El decreto suspensivo de derechos y garantías en la Constitución Política de los Estados Unidos Mexicanos - García Bibián, Jairo (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
The suspensive power of human rights is the constitutional tool available to Sovereign States, in the case of the Mexican State there is this suspensive figure in Article 29 of the Political Constitution of the United Mexican States, establishing in it the constitutional procedure to restrict or suspend throughout the country or in a specific place the exercise of some rights and guarantees that are an obstacle to dealing with human rights. the situation of cases of invasion, serious disturbance of the public peace or any other that puts society in serious danger or conflict. There are several conceptions of this optional tool available to states, such as that of Giorgio Agamben, who states that the state of exception is the vacuum of law; Hector Fix-Fierro, conceives of the power to suspend rights as an extraordinary measure of "legitimate defense" more loaded with criminal law; for Karl Lowenstein, the suspensive power is conceived as "the temporary substitution of the technique that distributes power in the hands of the governmental holder; and Ignacio Burgoa, addresses the conceptualization of suspension of human rights as that cessation of validity, on the legal relationship on which it depends. The suspensive power is the last resort of the State, to protect people, democracy and its sovereignty in extraordinary, serious and dangerous situations, be it invasions, natural disasters of great magnitude or deadly epidemics that threaten extermination as long as the most elementary rights of citizens are safeguarded.

La facultad suspensiva de los derechos humanos es la herramienta constitucional con la que cuentan los Estados Soberanos, en el caso del Estado Mexicano se cuenta con esta figura suspensiva en el artículo 29 de la Constitución Política de los Estados Unidos Mexicanos, estableciendo en él el procedimiento constitucional para restringir o suspender en todo el país o en lugar determinado el ejercicio de algunos derechos y garantías que fueren obstáculo para hacer frente a la situación de casos de invasión, perturbación grave de la paz pública o cualquier otra que ponga a la sociedad en grave peligro o conflicto. Son varias las concepciones que se tienen sobre esta herramienta facultativa con la que cuentan los estados, tales como la de Giorgio Agamben, pues afirma que el estado de excepción es el vacío de derecho; Hector Fix-Fierro, concibe a la facultad suspensiva de derechos como una medida extraordinaria de “legítima defensa” más cargada con el derecho penal; para Karl Lowenstein, la facultad suspensiva es concebida como “la sustitución temporal de la técnica que distribuye el poder en las manos del detentador gubernamental; e Ignacio Burgoa, aborda la conceptualización de suspensión de derechos humanos como aquella cesación de vigencia, sobre la relación jurídica de la que depende.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2025-1319; Procesal constitucional; Suspensión; Proceso; Proporcionalidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19434